Infectious bursal disease virus: identification of the novel genetic group and reassortant viruses - L. O. Scherbakova; Ye. V. Ovchinnikova; T. N. Zybina; S. N. Kolosov; N. G. Zinyakov; Z. B. Nikonova; D. B. Andreychuk; I. A. Chvala (Ветеринария сегодня)
The results of the phylogenic analysis of the nucleotide sequence of the IBDV A and B genome segments have been presented. Traditionally the IBDV isolates are classified based on the phylogenic analysis of the hypervariable region of the VP2 gene. The analysis of the VP2 gene segments of the isolates detected in the Russian Federation demonstrated that most of them belong to the genetic group comprising highly virulent IBDV isolates. However, not all isolates belonging to one genetic group have the same phenotypic characteristics. This is related to the fact that the virulence is determined not only based on the characteristics of the VP2 gene (A segment) but on the characteristics of the VP1 gene (B segment) as well. The IBDV genome segmentation allows formation of reassortant viruses which can be identified as a result of the genome segment analysis. The phylogenic analysis of the nucleotide sequences of VP2 and VP1 genes of 28 IBDV isolates detected at RF, Ukrainian and Kazakh poultry establishments in 2007 and 2019 showed that 15 of them are reassortant viruses. Different combinations of the genome segments have been identified among these reassortant viruses. Detection of different combinations of IBDV genome segments is indicative of the fact that the heterogeneous virus population circulates on the poultry farms. Pathogenicity studies of the three IBDV isolates showed that the most virulent was an isolate having two genome segments characteristic of the highly virulent virus. Two reassortant viruses having only one genome segment A or B, characteristic of the infectious bursal disease, demonstrated less pronounced virulent properties.